Preliminary findings on the experiences of care for parents who suffered perinatal bereavement during the COVID-19 pandemic - Sergio A. Silverio; Abigail Easter; Claire Storey; Davor Jurković; Jane Sandall; on behalf of the PUDDLES Global Collaboration (BMC, 2021)
Abstract Background The COVID-19 pandemic poses an unprecedented risk to the global population. Maternity care in the UK was subject to many iterations of guidance on how best to reconfigure services to keep women, their families and babies, and healthcare professionals safe. Parents who experience a pregnancy loss or perinatal death require particular care and support. PUDDLES is an international collaboration investigating the experiences of recently bereaved parents who suffered a late miscarriage, stillbirth, or neonatal death during the global COVID-19 pandemic, in seven countries. In this study, we aim to present early findings from qualitative work undertaken with recently bereaved parents in the United Kingdom about how access to healthcare and support services was negotiated during the pandemic. Methods In-depth semi-structured interviews were undertaken with parents (N = 24) who had suffered a late miscarriage (n = 5; all mothers), stillbirth (n = 16; 13 mothers, 1 father, 1 joint interview involving both parents), or neonatal death (n = 3; all mothers). Data were analysed using a template analysis with the aim of investigating bereaved parents' access to services, care, and networks of support, during the pandemic after their bereavement. Results All parents had experience of utilising reconfigured maternity and/or neonatal, and bereavement care services during the pandemic. The themes utilised in the template analysis were: 1) The Shock & Confusion Associated with Necessary Restrictions to Daily Life; 2) Fragmented Care and Far Away Families; 3) Keeping Safe by Staying Away; and 4) Impersonal Care and Support Through a Screen. Results suggest access to maternity, neonatal, and bereavement care services were all significantly reduced, and parents' experiences were notably affected by service reconfigurations. Conclusions Our findings, whilst preliminary, are important to document now, to help inform care and service provision as the pandemic continues and to provide learning for ongoing and future health system shocks. We draw conclusions on how to enable development of safe and appropriate services during this pandemic and any future health crises, to best support parents who experience a pregnancy loss or whose babies die.